Admissions to intensive care units from emergency departments: a descriptive study. Issue 6 (23rd May 2005) - Simpson, H K; Clancy, M; Goldfrad, C; Rowan, K
Abstract : Objectives: To describe the case mix, activity, and outcome for admissions to intensive care units (ICUs) from emergency departments (EDs). Design: An observational study using data from a high quality clinical database, the Case Mix Programme Database, of intensive care admissions, coordinated at the Intensive Care National Audit & Research Centre (ICNARC). Setting: 91 adult ICUs in England, Wales, and Northern Ireland, 1996–99. Subjects: 46 587 intensive care admissions. Main outcome measures: Ultimate hospital mortality. Results: Admissions from EDs constituted 26% of total admissions to ICU, 77% of which were direct admissions to ICU from EDs. Direct admissions from EDs, indirect admissions from EDs, and non-ED admissions presented to ICU with different conditions and severity of illness. Indirect admissions from EDs presented in the ICU with the more severe case mix (older age, more acute severity of illness, more likely to have a chronic illness) compared with direct admissions to ICU from EDs. Compared with ICU admissions not originating in EDs, unit and hospital mortality were higher for admissions from EDs, with indirect admissions experiencing the highest hospital (46.4%) mortality. For ICU survivors, indirect admissions stayed longest in the ICU. Conclusions: A large proportion of admissions to ICU (26%) originate in EDs, and differ from those not originating in EDs in terms of both case mix and outcome. Additionally, those admitted directly to ICU from EDs differ from those admitted indirectly via a ward. The observed differences in outcome between different admission routes require further investigation and explanation.